1996
DOI: 10.1007/bf02265049
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of a 31-bp bovine subrepeat in centromeric satellite DNA monomers ofCervus elaphus and other cervid species

Abstract: A centromeric satellite DNA clone was isolated from the genome of the European red deer (Cervus elaphus hippelaphus) and designated Ce-Pst1. This clone was localized to the centromeric region of all red deer chromosomes with the exception of a single pair of metacentric autosomes and the Y chromosome. DNA sequence analysis of the 806-bp Ce-Pst1 clone showed 73.0-78.9% sequence homology to four previously isolated cervid centromeric satellite DNA clones, suggesting that the Ce-Pst1 clone is yet another member o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 34 publications
(21 reference statements)
1
28
0
Order By: Relevance
“…Some studies suggested that the repetitive DNA families at or near the centromeric and telomeric regions might facilitate illegitimate recombination between non-homologous chromosomes of muntjacs (Brinkley et al, 1984;Bogenberger et al, 1985Bogenberger et al, , 1987Benedum et al, 1986;Lin et al, 1991Lin et al, , 2004Lee et al, 1994Lee et al, , 1997Scherthan, 1995;Lee & Lin, 1996;Yang et al, 1997b;Li et al, 2000aLi et al, , b, 2002Hartmann & Scherthan, 2004). At present, four satellite DNA families are found in Muntiacus: satellite DNA families I, II, IV and V (Bogenberger et al, 1985;Lin et al, 1991Lin et al, , 2004Li et al, 2000bLi et al, , 2005.…”
mentioning
confidence: 99%
“…Some studies suggested that the repetitive DNA families at or near the centromeric and telomeric regions might facilitate illegitimate recombination between non-homologous chromosomes of muntjacs (Brinkley et al, 1984;Bogenberger et al, 1985Bogenberger et al, , 1987Benedum et al, 1986;Lin et al, 1991Lin et al, , 2004Lee et al, 1994Lee et al, , 1997Scherthan, 1995;Lee & Lin, 1996;Yang et al, 1997b;Li et al, 2000aLi et al, , b, 2002Hartmann & Scherthan, 2004). At present, four satellite DNA families are found in Muntiacus: satellite DNA families I, II, IV and V (Bogenberger et al, 1985;Lin et al, 1991Lin et al, , 2004Li et al, 2000bLi et al, , 2005.…”
mentioning
confidence: 99%
“…Quite common features of satellite DNA are: i) the presence of internal direct and inverted subrepeats (Bogenberger et al, 1985;Lee, C. & Lin, 1996;Zhang & Horz, 1984); ii) the presence of the same satellite DNA families at the centromeres of autosomes and the X chromosome, but not at the Y chromosome centromere, like in mouse, sheep, and bat; iii) a greater divergence of the Y centromere sequence in comparison to the other centromeres, like in mouse and primates. Sheep, swine, and horse have a different satellite content in acrocentric and metacentric chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of this 31 bp motif across the entire length of the satellite I repeat suggests that its present structure could have arisen from a tandemly amplification of an ancestral ~31 bp unit. The 31-mer motif sequence has been found also in other bovine satellites, like satellite III (Plucienniczak et al, 1982;Taparowsky & Gerbi, 1982), and in the deer, muntjac, and pronghorn centromeric satellites (Bogenberger et al, 1985;Denome et al, 1994;Lee, C. & Lin, 1996), arguing that the amplification of the ~31 bp unit may have occurred in their common ancestral.…”
Section: Cetartiodactylamentioning
confidence: 89%
“…A very common feature of satellite DNAs is the presence of internal direct and inverted subrepeats (Zhang and Horz, 1984;Bogenberger et al, 1985;Lee and Lin, 1996). Nevertheless, no internal subrepeats were found in this satellite of P. pipistrellus.…”
Section: Sequence Analysis Of Cloned Monomersmentioning
confidence: 89%
“…Hence, the location of this repetitive DNA coincides with the location of the pericentromeric constitutive heterochromatin previously described. The presence of satellite DNA in the centromeres of autosomes and X chromosomes and its absence from the Y chromosome centromere is a common feature of satellite DNAs from other mammal species (Lee and Lin, 1996;Kunze et al, 1999;Fernández et al, 2001).…”
Section: Chromosome Localizationmentioning
confidence: 99%